The development and psychometrical evaluation of a set of instruments to evaluate the effectiveness of diabetes patient education. Issue 3 (2nd January 2013) - Duprez, Veerle; De, Marleen; De, Marc; Beeckman, Dimitri
<x xml:space="preserve">Abstract</x> Aims and objectives To develop a set of psychometrically sound instruments to assess knowledge, self‐management and self‐efficacy of diabetic patients. Furthermore, a survey to evaluate the satisfaction about diabetes education for patients was developed and tested. Background Treatment and secondary prevention of diabetes require a complex combination of care components. Patients' education has been accepted to improve diabetes knowledge, self‐management and self‐efficacy. Psychometrically sound instruments are needed to measure these patient‐centred outcomes. Design Psychometric instrument validation. Methods The first phase included a systematic literature review to develop the instruments. Content validity was evaluated using a two‐round Delphi procedure involving diabetes experts. The content validity of the instruments was excellent. In a second phase, a convenience sample of 188 diabetic patients in two hospitals in one specific care region in Belgium participated in the psychometric evaluation. The criterion‐related validity and internal consistency reliability were evaluated. Results The study produced a 21‐item knowledge instrument, reflecting knowledge about 'glycemic control' and 'medico‐social management aspects'. The self‐management instrument included 32 statements, reflecting 'treatment and compliance' and 'general lifestyle'. The self‐efficacy instrument included 30 items, reflecting 'nutrition', 'treatment' and 'regimen'. The patient satisfaction survey included 36 items, reflecting satisfaction about the relationship among the diabetes specialist, the diabetes educator, podiatrist and dietician. Conclusions An instrument set with sound psychometric characteristics was developed to assess knowledge, self‐management and self‐efficacy of diabetic patients. Future studies should focus on the association between the instrument outcomes and clinical patient outcomes. Relevance to clinical practice The current instrument can support the design of educational interventions and training programmes and reduce inconsistencies in the information that patients receive. Furthermore, the instruments can be used for benchmarking the quality of diabetic patient education.